Identification and differentiation of pathogenic and non–pathogenic serotypes of fowl adenoviruses using PCR-RFLP and sequencing - PARTHIBAN, M; SHALINI, K S; KUMANAN, K; JAYARAMAN, J (The Indian Journal of Animal Sciences, 2013)
Two cell culture adapted non-pathogenic isolates and 5 cell culture adapted pathogenic isolates of fowl adenoviruseswere amplified using hexon gene H1/H2 and H3/H4 primers. The H1/H2 and H3/H4 PCR products were digested withHaeII and HpaII respectively. The species and serotype of our FAV isolates were arrived by comparing the polymerasechain reaction – restriction fragment length polymorphism pattern of FAV 1–12 reference strains. Out of 7 isolates,RFLP pattern of 2 isolates matched exactly either with RFLP pattern of both HaeII and HpaII enzymes or any oneenzyme of FAV reference strains. Four of our pathogenic isolates and 1 non-pathogenic were not matching with RFLPpattern of reference strains. The 5 isolates which gave different restriction pattern later confirmed as species D (serotype 2) and species C (serotype 4) based on nucleotide sequence data on blast analysis. Hence, BLAST analysi   using nucleotide sequence data may be used as effective  tool for serotype identification of FAV field isolates. More interestingly, the prevalence of 2 non-pathogenic serotypes  in 1 poultry farm in the same period was recorded. Earlier hydropericardium syndrome/inclusion body hepatitis was associated with serotype 4 in India. However, in recent outbreaks of inclusion body hepatitis in Tamil Nadu,              prevalence of pathogenic serotype 2 in vaccinated flock was recorded, and serotype 4 was found to be non-pathogenic. Based on polymerase chain reaction-restriction fragment length polymorphism pattern, pathogenic and non-pathogenic field isolates of serotype 2 and serotype 4 could be differentiated.